Comparison of bacterial colonies adherence on silk and catgut sutures in odontectomy patient at Dr. Pirngadi Hospital - Rahmi Syaflida; Olivia A. Hanafiah; Ahyar Riza; Muhammad R. Fauzie (DiscoverSys Inc., 2021)
Objective:To compare the different amount of bacterial colonies adhered on silk and catgut sutures in odontectomy patient at Dr. Pirngadi Hospital from May to July 2018.Material and Methods:This is laboratory experimental study with a â€œpost-test only control groupâ€ design which means the threads that have been remove on 7th day postoperative and would be transferred to Microbiology Laboratory, Faculty of Mathematic and Science, Universitas Sumatera Utara . Bacterial colony counter were used to count the amount of bacteria colony on a petri dish containing PCA medium after the colonization was diluted to 10-7 mL. The number of patients studied were 26 people, therefore 13 people used silk sutures and 13 people used catgut sutures.Results:The results were statistically analyzed using Mann-Whitney Test. There was no significant difference (p> 0.05) between the amount of bacterial colonies adherence on silk and catgut sutures. The mean bacterial colony on silk sutures are 207.38Â±173.605 x107 CFU/mL, meanwhile on catgut sutures are 115.15Â±158.905 x107 CFU/mL. Conclusion:Catgut suture could minimalize bacterial colonization better than silk suture.Â